2005
DOI: 10.4018/jgim.2005070104
|View full text |Cite
|
Sign up to set email alerts
|

Information Systems Effectiveness in Small Businesses

Abstract: This study examines the applicability of the Thong, Yap, and Raman (1996) model of information systems (IS) effectiveness tested among Singaporean small businesses in a Canadian context. The model evaluates the importance of managerial support and external expertise (vendors and consultants) for IS effectiveness. This study extends the Thong et al. model by adding an intention of expansion construct. The sample included 105 small business users of IS in a small city in western Canada. The results show that bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
38
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 22 publications
2
38
0
Order By: Relevance
“…In fact, many studies have found that firm size is directly associated with AIS effectiveness (de Guinea et al, 2005). The concept of "resource poverty" could provide an explanation for this uniqueness.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In fact, many studies have found that firm size is directly associated with AIS effectiveness (de Guinea et al, 2005). The concept of "resource poverty" could provide an explanation for this uniqueness.…”
Section: Introductionmentioning
confidence: 99%
“…As a knowledge-based economy emerges, information is considered crucial for the survival of any organization, including a SME (de Guinea et al, 2005). The globalization of products, services, markets, and competition has increased the need for flexibility, quality, cost effectiveness, and timeliness (Hunter et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations